Two-Year Follow-Up of Parathyroid Hormone, Calcium, and Vitamin D Serum Levels in a Patient after Parathyroidectomy - Alexander Kam; Dinda Aprilia; Eva Decroli; Syafril Syahbuddin (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2025)
Parathyroidectomy is the definitive treatment for primary hyperparathyroidism. Because of the hungry bone syndrome and prolonged hypocalcemia risk, we must follow up on a patient's parathyroid hormone, calcium, and vitamin D serum after parathyroidectomy. In this case report, we reported on a parathyroidectomy patient whom we followed for two years and who, interestingly, had elevated parathyroid hormone levels. A 35-year-old male patient diagnosed with a left parathyroid tumor underwent parathyroidectomy and isthmolobectomy. The patient was treated with calcium, vitamin D, and levothyroxine supplementation. We diagnosed the patient with hungry bone syndrome on the fourth day of post-parathyroidectomy. Then, we documented calcium, vitamin D, and PTH levels in the next two years. The calcium levels are 7.2 (June 2022), 8.2 (July 2022), 8.5 (September 2022), 7.8 (October 2022), 8.1 (June 2023), 9.7 (June 2024). The PTH levels are 244.2 (June 2022), 328.3 (July 2022), 306.5 (September 2022), 457.2 (October 2022), 163.3 (June 2023), 34.4 (June 2024). The Vitamin D levels are 34.4 (July 2022), 13.4 (March 2023), 35.2 (September 2023), 50.4 (April 2024). We increased the dose of calcium and vitamin D supplementation. The patient is in good condition and has reached a normal level of these laboratory parameters in the second year post-parathyroidectomy. PTH, calcium, and vitamin D serum are needed for follow-up in patients after parathyroidectomy. Normalizing calcium and vitamin D serum is essential to maintaining a normal PTH level. Normal PTH, calcium, and vitamin D serum are the cure indications in this patient.